2021
DOI: 10.1021/acsami.1c09294
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of FLT4-Targeted Nanocarriers Enhances Cell-Softening Glaucoma Therapy

Abstract: Primary open-angle glaucoma is associated with elevated intraocular pressure (IOP) that damages the optic nerve and leads to gradual vision loss. Several agents that reduce the stiffness of pressure-regulating Schlemm’s canal (SC) endothelial cells, in the conventional outflow pathway of the eye, lower IOP in glaucoma patients and are approved for clinical use. However, poor drug penetration and uncontrolled biodistribution limit their efficacy and produce local adverse effects. Compared to other ocular endoth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Cytotoxicity and systemic effects remain to be investigated for both delivery systems. Cell-softening agents, such as ligands targeting FLT-4/VEGFR3 receptors, were delivered through modified micelles, improving receptor targeting and lowering IOP [ 89 ]. Further improvement in corneal permeability and sustained release is required, given that effects remained up to only 48 h. Nanosuspensions were also reported to deliver acetazolamide by Donia et al (2020), where they demonstrated sustained drug release, improved acetazolamide solubility, and thereby improved bioavailability [ 90 ].…”
Section: Nano-based Dds For Glaucomamentioning
confidence: 99%
“…Cytotoxicity and systemic effects remain to be investigated for both delivery systems. Cell-softening agents, such as ligands targeting FLT-4/VEGFR3 receptors, were delivered through modified micelles, improving receptor targeting and lowering IOP [ 89 ]. Further improvement in corneal permeability and sustained release is required, given that effects remained up to only 48 h. Nanosuspensions were also reported to deliver acetazolamide by Donia et al (2020), where they demonstrated sustained drug release, improved acetazolamide solubility, and thereby improved bioavailability [ 90 ].…”
Section: Nano-based Dds For Glaucomamentioning
confidence: 99%
“…For example, as recently reported, targeting ligands with a longer spacing PEG linker can better extend themselves from the micelle surface to avoid the crowded surface environment and allow for engagement with endocytic cell receptors. [ 222 ]…”
Section: Delivery Of Peptidesmentioning
confidence: 99%
“…For example, as recently reported, targeting ligands with a longer spacing PEG linker can better extend themselves from the micelle surface to avoid the crowded surface environment and allow for engagement with endocytic cell receptors. [222] In addition to conjugating hydrophobic tails onto a single peptide domain, peptide amphiphiles also can be synthesized by polymerizing peptide-containing monomers into amphiphilic polymer brushes. This concept has been extensively explored by the Gianneschi group, and is named peptidepolymer amphiphile (PPA).…”
Section: Peptide Amphiphile Nanoparticlesmentioning
confidence: 99%
“…Here, we develop a gene delivery system employing self-assembling block copolymer nanocarriers engineered for efficient cytosolic delivery of pDNA via incorporation of a cationic DP block ( Figure 1 ). We have previously demonstrated that poly (ethylene glycol)-block-poly (propylene sulfide) (PEG- b -PPS) nanocarriers effectively target macrophages and dendritic cells ( Vincent et al., 2021a ; Yi et al., 2016 , 2019 ), are capable of delivering diverse payloads intracellularly ( Allen et al., 2017 , 2018a bib_Allen_et_al_2017 ; Bobbala et al., 2020 ; Scott et al., 2012 ; Stack et al., 2020 , 2021 ; Vasdekis et al., 2012 ; Vincent et al., 2021c ), are non-immunogenic in human blood ( Vincent et al., 2021b ), and are both non-inflammatory and non-toxic in non-human primates ( Allen et al., 2018b ), humanized mice ( Dowling et al., 2017 ), and diverse mouse models of disease ( Yi et al., 2016 ). Furthermore, PEG- b -PPS copolymers can be formulated to permit the rapid self-assembly of nanostructures encapsulating biologic payloads upon the addition of aqueous medium ( Bobbala et al., 2021 ), which extends their practical usage to industrial or clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the peptide aspects of our technology, the PEG- b -PPS polymers contribute multiple useful features for gene delivery. For example, PEG- b -PPS provides oxidation sensitivity via its hydrophobic PPS blocks that stabilize the nanostructure and enable disassembly within acidic endolysosomal compartments ( Bobbala et al., 2020 ; Scott et al., 2012 ; Stack et al., 2020 ; Vasdekis et al., 2012 ; Vincent et al., 2021c ). The hydrophilic methoxy-terminated PEG corona serves to improve biocompatibility and reduce toxicity ( Allen et al., 2018b ; Vincent et al., 2021b ).…”
Section: Introductionmentioning
confidence: 99%